Development of an Outdoor Laboratory-Based Discovery Learning Model on the Characteristics of Living Things to Improve Students' Science Literacy and Science Process Skills at MTsN 3 Banda Aceh - Noviyanti; Jalaluddin; Evi Apriana; Yuhasriati; Aiza Rafsanjani (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an outdoor laboratory-based Discovery Learning model on the characteristics of living things to improve scientific literacy and science process skills of students at MTsN 3 Banda Aceh. The method used is development research with the 4D model (Define, Design, Develop, Disseminate). Product validation was carried out by material experts and learning experts, while practicality was measured through teacher and student responses, and effectiveness was measured by N-gain and paired sample t-test. The validation results of material experts reached 85.27% and 85%, learning experts 84% and 86% (valid category). Teacher responses were 86.25% and student responses 86.62% (strong category). The N-gain value was 0.73 (high criteria) with a T-test significance value of 0.000 <0.05. It was concluded that the outdoor laboratory-based Discovery Learning model is valid, practical, and very effective in improving students' scientific literacy and science process skills.